Airborne particulate matter exposure and urinary albumin excretion: the Multi-Ethnic Study of Atherosclerosis. Issue 8 (21st November 2007) - O'Neill, M S; Diez-Roux, A V; Auchincloss, A H; Franklin, T G; Jacobs, D R; Astor, B C; Dvonch, J T; Kaufman, J
Abstract : Objectives: Understanding mechanistic pathways linking airborne particle exposure to cardiovascular health is important for causal inference and setting environmental standards. We evaluated whether urinary albumin excretion, a subclinical marker of microvascular function which predicts cardiovascular events, was associated with ambient particle exposure. Methods: Urinary albumin and creatinine were measured among members of the Multi-Ethnic Study of Atherosclerosis at three visits during 2000–2004. Exposure to PM2.5 and PM10 (μg/m 3 ) was estimated from ambient monitors for 1 month, 2 months and two decades before visit one. We regressed recent and chronic (20 year) particulate matter (PM) exposure on urinary albumin/creatinine ratio (UACR, mg/g) and microalbuminuria at first examination, controlling for age, race/ethnicity, sex, smoking, second-hand smoke exposure, body mass index and dietary protein (n = 3901). We also evaluated UACR changes and development of microalbuminuria between the first, and second and third visits which took place at 1.5- to 2-year intervals in relation to chronic PM exposure prior to baseline using mixed models. Results: Chronic and recent particle exposures were not associated with current UACR or microalbuminuria (per 10 μg/m 3 increment of chronic PM10 exposure, mean difference in log UACR = −0.02 (95% CI −0.07 to 0.03) and relative probability of having microalbuminuria = 0.92 (95% CI 0.77 to 1.08)) We found only weak evidence that albuminuria was accelerated among those chronically exposed to particles: each 10 μg/m 3 increment in chronic PM10 exposure was associated with a 1.14 relative probability of developing microalbuminuria over 3–4 years, although 95% confidence intervals included the null (95% CI 0.96 to 1.36). Conclusions: UACR is not a strong mechanistic marker for the possible influence of air pollution on cardiovascular health in this sample.